Farming systems research strategy for the development of inland valleys for increased food production in West Africa - Spencer, D. (1991)
This paper describes a research strategy for the inland valleys which are flat-bottomed and vary in size from a few to hundreds of hectares. Most of the valleys are not presently cultivated. Where cultivated, rice is the most important crop grown in the wet season followed usually by cultivation in the dry seasons of dry land crops such as sweet potatoes, cassava, groundnuts, maize and short season vegetables. Many attempts have been made in the past to introduce water control schemes into these valleys. Much of the available evidence shows that the economic return to this investment has been marginal. AIso, crop and resources management problems are more important than other constraints in the valleys. The paper proposes a research strategy that would concentrate on producing improved technologies for valleys in which there is minimum or no water control. This would involve increased emphasis on the linkages between technologies used in the wet and dry season.